Satiric Inheritance : Rabelais to Sterne - Seidel, Michael, 1943- (Book collections on Project MUSE., 1979)
Arguing that satiric potential is latent in virtually all dispensation, succession, and inheritance narratives, Michael Seidel suggests a new and comprehensive understanding of satire's place in the more general context of narrative theory. The notion of inheritance shares with traditional narrative action the need to transmit and preserve form.Originally published in 1979.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.